THE EFFECT OF PROVIDING TUBERCULOSIS EDUCATIONAL VIDEOS ON THE LEVEL OF TUBERCULOSIS KNOWLEDGE AMONG UNIVERSITY OF ISLAM MALANG MEDICAL FACULTY STUDENTS CLASS OF 2024 - Zakiyah, Rima; Zulkarnain, Alex Andria; Arioseto, Bagas; Yofa, Muhammad Davin Darian; Waliudini, Hellido Ariya; Wijayanto, Fajra Kusuma Ningrum; Rahmaniah, Safina Aisyah; Resty, Muthi’ah; Priambudi, Yomabinanda Luhur; Ramadhan, Eria Nada; Nabilah, Althavfia (Jurnal Kesehatan Islam : Islamic Health Journal, 2025)
Introduction: Tuberculosis (TB) is an infectious disease caused by the bacterium Mycobacterium tuberculosis, which mainly affects the lungs. TB is still one of the biggest public health problems in the world. According to a World Health Organization (WHO) report, by 2023 there will be approximately 10.6 million new TB cases globally, with 1.6 million deaths from the disease, making it one of the top 10 leading causes of death in the world. Methods: This study uses a descriptive quantitative approach, used to evaluate the effectiveness of counseling by measuring the level of knowledge of UNISMA Faculty of Medicine students class of 2024 before and after receiving information through direct counseling with educational video media. Results: Data analysis using paired t-test showed a significant difference between pre-test and post-test scores, with an average pre-test score of 68.6813 and an average post-test score of 90.1099. A significance value of <0.001 indicates that this increase in knowledge is the result of the educational intervention. Conclusion: The study conducted on UNISMA Faculty of Medicine students class of 2024 proved that the educational program on Tuberculosis (TB) is very effective in increasing students' knowledge about TB. keywords: Faculty of Medicine students class of 2024, TB educational video, level of TB knowledge